2016
DOI: 10.3892/mmr.2016.5648
|View full text |Cite
|
Sign up to set email alerts
|

Cabazitaxel-induced autophagy via the PI3K/Akt/mTOR pathway contributes to A549 cell death

Abstract: Cabazitaxel has been used to treat castration-resistant prostate cancer since its approval by the US Food and Drug Administration in 2010. However, whether cabazitaxel may inhibit the proliferation of other tissue-derived cancer cells, and its underlying mechanism, remains unknown. In the present study, the A549 lung adenocarcinoma cancer cell line was exposed to cabazitaxel, in order to investigate its cytotoxic effect and determine the underlying mechanism. The results demonstrated that cabazitaxel was able … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 38 publications
2
26
0
Order By: Relevance
“…We refer the reader to a thorough review that has highlighted many studies showing ADCD by various agents in different cancer cell types, such as the BH3 mimetics obatoclax and gossypol, histone deacetylase inhibitors, as well as the natural plant products resveratrol and betulinic acid (Fulda and Kögel, 2015). Additionally, more recent studies that have clearly demonstrated autophagy gene-dependent cell death in the absence of apoptosis include the treatment of glioma cells with a combination of the tricyclic antidepressant imipramine (IM) and the anti-platelet drug ticlopidine (TIC; an inhibitor of ADP receptor P2Y 12 ) (Shchors et al, 2015), the treatment of lung carcinoma cells with cabazitaxel (Huo et al, 2016) and the treatment of hepatocellular carcinoma with the natural flavonoid kaempferol (Han et al, 2017). Importantly, ADCD triggered by IM and TIC has also been associated with slower tumor progression and improved survival in in vivo mouse glioma models; knockdown of Atg7 in the glioma cells attenuates the effects of the drugs on survival and tumor growth (Shchors et al, 2015).…”
Section: Adcd In Pathophysiological Conditionsmentioning
confidence: 99%
“…We refer the reader to a thorough review that has highlighted many studies showing ADCD by various agents in different cancer cell types, such as the BH3 mimetics obatoclax and gossypol, histone deacetylase inhibitors, as well as the natural plant products resveratrol and betulinic acid (Fulda and Kögel, 2015). Additionally, more recent studies that have clearly demonstrated autophagy gene-dependent cell death in the absence of apoptosis include the treatment of glioma cells with a combination of the tricyclic antidepressant imipramine (IM) and the anti-platelet drug ticlopidine (TIC; an inhibitor of ADP receptor P2Y 12 ) (Shchors et al, 2015), the treatment of lung carcinoma cells with cabazitaxel (Huo et al, 2016) and the treatment of hepatocellular carcinoma with the natural flavonoid kaempferol (Han et al, 2017). Importantly, ADCD triggered by IM and TIC has also been associated with slower tumor progression and improved survival in in vivo mouse glioma models; knockdown of Atg7 in the glioma cells attenuates the effects of the drugs on survival and tumor growth (Shchors et al, 2015).…”
Section: Adcd In Pathophysiological Conditionsmentioning
confidence: 99%
“…As a member of the PI3K-related kinase family, mTOR is associated with cell proliferation and cell metabolism. Previous studies have shown that inhibition of AKT and its downstream target mTOR contributes to the initiation of autophagy [35]. Meanwhile, mTOR is an important downstream target of PI3K/AKT and positively regulates p70S6K; PI3K/AKT/mTOR is an important intracellular signaling pathway in regulating cell survival and death.…”
Section: Discussionmentioning
confidence: 99%
“…A novel hybrid of the 3-benzyl coumarin seco-B-ring derivative and phenylsulfonylfuroxan (compound 6) reduces the phosphorylation levels of mTOR-S2448, Akt-S373, and the downstream p70s6K-S371 and 4EBP1-pT45 proteins in a concentration-/time-dependent manner to induce autophagy and apoptosis of A549 cells [56]. The antiprostate-cancer drug, cabazitaxel, also inhibits proliferation of A549 cells through autophagy which is regulated by the PI3K/Akt/mTOR pathway [57]. Ophiopogon japonicus is a traditional medicinal plant, and its main components are flavonoids and steroidal saponins.…”
Section: Drugs That Target Pi3k/akt/mtor Pathwaymentioning
confidence: 99%